2018
DOI: 10.1108/pmm-11-2017-0053
|View full text |Cite
|
Sign up to set email alerts
|

Academic libraries and student learning outcomes

Abstract: Purpose The purpose of this paper is to examine the literature on student learning outcomes and academic libraries. An analysis of 81 papers revealed the following themes: outcomes assessment of library skills instruction, tools for assessing students’ achievement of learning outcomes, institutional accreditation and student learning outcomes, academic libraries’ impact on student learning outcomes, and the creation of learning outcomes. An understanding of these themes highlights how student learning outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…This finding is supported by previous studies. According to [26], the role and involvement of academic librarians in supporting the educational mission through their instructional efforts that result in student learning outcomes would increase the visibility and value of the academic library to the parent institution. On the contrary, as pointed out by [16], students' failure to comprehend and acknowledge the roles and skills of academic librarians is the root cause of their underutilization of library resources and services.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by previous studies. According to [26], the role and involvement of academic librarians in supporting the educational mission through their instructional efforts that result in student learning outcomes would increase the visibility and value of the academic library to the parent institution. On the contrary, as pointed out by [16], students' failure to comprehend and acknowledge the roles and skills of academic librarians is the root cause of their underutilization of library resources and services.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support earlier research by Goodall and Pattern (2011), who found that students who read more frequently achieved higher grades. Other research has also shown that academic libraries have a positive impact on student learning outcomes and learning production (Blummer and Kenton, 2018;Emmons and Martin, 2002;Hufford, 2016). The more learners engaged with the document, the more likely they were to view the full text and increased interest led to increased engagement.…”
Section: 21mentioning
confidence: 99%
“…According to studies, library support comprises providing users with information sources, materials, programs, and expertise to use WBLIS. Blummer and Kenton (2018) emphasize academic librarians' initiatives to improve student learning outcomes. They found that offering library skills education and monitoring student learning outcomes would boost the visibility and worth of academic libraries to their parent institutions.…”
Section: Literature Reviewmentioning
confidence: 99%